Effect of penicillamine therapy on circulating immune complexes in rheumatoid arthritis. Issue 5 (October 1976) - Mohammed, Idris; Barraclough, D.; Holborow, E. J.; Ansell, Barbara M.
Abstract : Mohammed, I., Barraclough, D., Holborow, E. J., and Ansell, B. M. (1976). Annals of the Rheumatic Diseases, 35, 458-462. Effect of penicillamine therapy on circulating immune complexes in rheumatoid arthritis. The sera of 40 patients with severe progressive rheumatoid arthritis were examined for the presence of soluble immune complexes before penicillamine therapy was started, and again after treatment for a mean period of 14·4 months. The methods used were radiobioassay (macrophage uptake), Clq-binding capacity, and precipitation by 4% polyethylene glycol. Before treatment the sera of 37 patients showed significantly enhanced uptake of 125 I-labelled aggregated human IgG by guinea pig macrophages. Treatment produced significant falls in mean erythrocyte sedimentation rate, differential agglutination titre, and serum IgG and IgM levels, and enhancing complexes (EC) decreased or disappeared in 20 patients. In 9 patients EC changed to inhibiting complexes, and in 8 EC levels were unchanged. In 6 of 8 patients with cutaneous vasculitis initially, both lesions and EC disappeared. The total protein and the IgG and IgM precipitated from patients' sera by 4% polyethylene glycol fell significantly on treatment. Antinuclear antibody titres were unchanged by penicillamine, and 3 patients acquired these antibodies during treatment. These findings suggest that penicillamine treatment in rheumatoid arthritis reduces the level of circulating soluble immune complexes in which IgM rheumatoid factor is a component.